Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data - Deng, Wenbo; Liu, Yuchao; Wang, Zongqing; Che, Yanli (European Journal of Taxonomy, 2020)
In this study, we examine 500 specimens of Anaplecta collected from China, of which 26 samples were used for COI sequencing. We confirm eight new species, i.e., Anaplecta corneola Deng & Che sp. nov., Anaplecta staminiformis Deng & Che sp. nov., Anaplecta arcuata Deng & Che sp. nov., Anaplecta strigata Deng & Che sp. nov., Anaplecta furcata Deng & Che sp. nov., Anaplecta cruciata Deng & Che sp. nov., Anaplecta nigra Deng & Che sp. nov. and Anaplecta bicolor Deng & Che sp. nov. based on morphological and molecular data using ABGD and GMYC analyses. The results of ABGD and GMYC were basically consistent with the morphospecies of Anaplecta. The intraspecific and interspecific genetic distances of Anaplecta ranged from 0 to 6.6% and 16.8% to 31.8%, respectively. We found the male genitalia of Anaplecta to exhibit intraspecific variation, especially in the phallomeres.